Exploring the prospects for a shared vision of offshore wind energy at the national level - Jamie Jenkins; Maria Malho; Jenni Kilpi; Kari Hyytiäinen (Marine Policy, 2026)

Regionally extended shared socioeconomic pathways for the offshore wind industry in Finland - Jamie Jenkins; Maria Malho; Kari Hyytiäinen (Energy, Ecology and Environment, 2022)
Offshore wind energy is increasingly becoming an important part of European and global low-emission power systems. The aims of this paper are to create a shared understanding on the major drivers of offshore wind development in Finland and to explore how these drivers, and opportunities for the entire industry, may develop over the twenty-first century, under different global futures. This research develops extended shared socioeconomic pathway (SSP) narratives for the offshore wind industry by using a virtual participatory workshop with expert stakeholders. According to our results, the five key drivers shaping the prospects of offshore wind development are public acceptability of offshore energy, global and national demand for low-emission energy, technological development and relative competitiveness of offshore energy, availability of space and wind resources, and energy markets and transmission infrastructure. Nationally extended SSP narratives, building on these key drivers, describe a wide range of alternative future risks and opportunities for developing offshore energy. Under sustainable development (SSP1), offshore wind is likely to soon become a major source of energy in the area, if developed in a balanced manner alongside other uses of the marine space. Under fossil-fuelled development (SSP5), offshore wind grows slower and may experience rapid uptake only in the latter half of the century. Under the regional rivalry scenario (SSP3), the need for local energy sources drives the national energy policies and may create new opportunities for offshore wind. Under the inequality scenario (SSP4), local municipalities and the residents decide on locations of new wind turbines and the overall magnitude of future offshore wind.